2017
DOI: 10.1073/pnas.1618114114
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of signal propagation in Physarum polycephalum

Abstract: Complex behaviors are typically associated with animals, but the capacity to integrate information and function as a coordinated individual is also a ubiquitous but poorly understood feature of organisms such as slime molds and fungi. Plasmodial slime molds grow as networks and use flexible, undifferentiated body plans to forage for food. How an individual communicates across its network remains a puzzle, but Physarum polycephalum has emerged as a novel model used to explore emergent dynamics. Within P. polyce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
84
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 42 publications
1
84
0
Order By: Relevance
“…Composition of a set of networks basic topologies [110] Rules for biologically inspired design adaptive networks [107] Creating minimum transport networks [108] Decision making and "scatter" or state of indecision between different attractors for foraging [95] Adaptation Morphodynamic changes that depend on the environment for motility [119] Adaptation Rules for Biologically Inspired Design Adaptive Networks [107] The stimulus comes from attractants or repellants (external) provides the impetus for morphological adaptation [109]. Maximizing internal flows by adapting patterns of contraction to size [120].…”
Section: Distribution Of Nutrients [4]mentioning
confidence: 99%
“…Composition of a set of networks basic topologies [110] Rules for biologically inspired design adaptive networks [107] Creating minimum transport networks [108] Decision making and "scatter" or state of indecision between different attractors for foraging [95] Adaptation Morphodynamic changes that depend on the environment for motility [119] Adaptation Rules for Biologically Inspired Design Adaptive Networks [107] The stimulus comes from attractants or repellants (external) provides the impetus for morphological adaptation [109]. Maximizing internal flows by adapting patterns of contraction to size [120].…”
Section: Distribution Of Nutrients [4]mentioning
confidence: 99%
“…The concept of acropetal and basipetal cytoplasmic flows within a fungal colony is not new. Previous studies demonstrated bidirectional nutrient translocation within cords or rhizomorphs of saprophytic and ectomycorrhizal basidiomycetes [8,10,20,23,41,47,48]. Bidirectionality was explained to be due to dedicated acro-and basipetally oriented hyphal bundles within cords or rhizomorphs.…”
Section: Discussionmentioning
confidence: 95%
“…Bidirectionality was explained to be due to dedicated acro-and basipetally oriented hyphal bundles within cords or rhizomorphs. The use of periodic cytoplasmic flows to increase the dispersion of a molecule was also described for the network of syncytical veins in the slime mold Physarum polycepharum [48,49]. Tlalka et al showed for the first time that N transport (2-aminoisobutyric acid, [ 14 C]AIB) within cords of Phaenerochate velutina underlies a certain periodicity that was dependent on the subdomain of mycelium observed [50].…”
Section: Discussionmentioning
confidence: 99%
“…Fluid flows are fundamental to the functioning of all organisms. They play an important role in homeostasis, by spreading resources and biochemical signals [1], [2], [3]. They power deformations driving migration of many motile cells [4], [5], [6], and can even directly impact on organism size [7].…”
Section: Introductionmentioning
confidence: 99%
“…Again, flows are known to power organism migration [6], [20]. Moreover, stimulants that alter cortex contractility have recently been found to be advected with the fluid flows inside the cell [2]. This observation suggests that the physical transport by fluid flows is the key to longranged spatial coordination of cortex contractions and fluid flows.…”
Section: Introductionmentioning
confidence: 99%